Post-operative outcomes of trans-abdominal pre-peritoneal mesh repair (TAPP) for groin hernia - Khan, Muhammad Waleed; Khan, Muhammad Talha; Majeed, Shahid; Khan, Raheel (International Journal of Pathology, 2025)
Background: Transabdominal preperitoneal (TAPP) repair has established itself as an effective laparoscopic technique for the treatment of groin hernia. The aim of the current study was to evaluate the early outcomes of TAPP repair for groin hernia and to assess the postoperative complications. Methods: This study enrolled 80 male patients with groin hernia over a 3-year period from January 2021 to December 2023. All patients underwent preoperative anesthesia assessment and gave written informed consent. A standard 3-port TAPP procedure was performed in which a 15x15 cm polypropylene mesh with absorbable pins was used in all cases and the peritoneal flap was closed with an absorbable continuous suture. Drains were placed in selected cases. Postoperative outcomes were assessed during the admission and readmission period. Results: All 80 patients were male with a mean age of 51.97±13.5 years. Primary hernias were observed in 56 patients (70%) with 20 (25%) left-sided and 36 (45%) right-sided cases. Bilateral hernias were present in 12 patients (15%), with 8 (10%) operated on the left side and 4 (5%) on the right side. Recurrent hernias were found in 12 patients (15%), including 4 (5%) left recurrent and 8 (10%) right recurrent cases. Postoperative complications included fever in 10 patients (12.5%), abscess formation in 6 patients (7.5%), seroma in 8 patients (10%), constipation in 6 patients (7.5%), and dysuria in 4 patients (5%). Pain assessment using VAS demonstrated significant improvement from preoperative levels (6.8 ± 1.4) to postoperative day 1 (2.1 ± 0.9) and at discharge (1.2 ± 0.6), with p<0.001 for both comparisons. Conclusion: Our experience with laparoscopic TAPP inguinal hernia repair demonstrates acceptable operative outcomes with low major complication rates.